Diomedes Komninos - Skarlatos, Dimitrios (My University, 2026)
'Diomidis Komninos' award-scholarship, from NTUA, being the first in rank student accepted in the Department of Surveying, after nationwide exams for entrance in higher education
Keywords: Education